Commentary: Integrating callous and unemotional traits into the definition of antisocial behaviour – a commentary on Frick et al. (2014). (June 2014) - Rowe, Richard
<x xml:space="preserve">Abstract</x> Heterogeneity in the presentation, antecedents, prognosis and treatment response of antisocial behaviour has long provided a challenge to developmental psychopathology researchers. As illustrated in the incisive Frick and colleagues' Annual Research Review, there is growing evidence that the presence of high callous‐unemotional (CU) traits identifies a subgroup of antisocial young people with a particularly aggressive and pervasive form of disorder. Frick and colleagues extend their developmental psychopathology approach to CU traits by linking in theories of conscience development and considering evidence on the stability of CU traits. This commentary addresses these themes and the area more generally, considering (1) comparison of a CU specifier to alternative approaches to antisocial heterogeneity (2) high CU traits in the absence of antisocial behaviour and (3) aspects of the measurement of CU traits.